Securitization of the Forced Labor Issue of Indonesian Migrant Fishing Vessel Crew by the Ministry of Foreign Affairs - Ladienda, Lu'lu' Mamluatul Hikmah; Hidayatullah, Nur Luthfi (UI Scholars Hub, 2026)
The case of forced labor against Indonesian migrant fishing vessel crew members has put the government in a dilemmatic position. The Indonesian government acts both as a labor sender and the protector of citizens' rights overseas. This study aims to examine how the Ministry of Foreign Affairs of the Republic of Indonesia raises the issue of forced labor as an existential threat through a securitization process. Using a descriptive qualitative approach, data was obtained from semi-structured interviews with officials of the Directorate of Indonesian Citizen Protection, as well as analysis of official documents, public statements, and credible media sources. The results show that the Ministry of Foreign Affairs actively carried out six stages of securitization, i.e. acting as the main actor, establishing migrant fishing vessel crew as the referent object, framing the existential threat, conveying speech acts through diplomatic channels, gaining legitimacy from the audience, and implementing extraordinary measures such as repatriation, diplomatic notes, strengthening bilateral cooperation, and public awareness campaigns. These findings confirm that the protection of Indonesian citizens by the Ministry of Foreign Affairs is no longer purely administrative, but has become part of a broader and more structured foreign security strategy.